2015
DOI: 10.21098/bemp.v17i2.48
|View full text |Cite
|
Sign up to set email alerts
|

Penentu Keberhasilan Redenominasi Mata Uang: Pendekatan Historis Dan Eksperimental

Abstract: Redenomination is a simplification of nominal value of currency by reducing digit (zero number) without reducing the real value of the currency. The main objective of this research was to examine whether the economic conditions at the time of redenomination may affect the success of currency redenomination. The methods used were regression analysis on historical data of 30 countries which are involved in redenominating their currencies, economic experiments with t-test, and survey of people’ perspective. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
14

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 9 publications
1
4
0
14
Order By: Relevance
“…Concerns of the community are quite reasonable considering that the sanering policies that are put in place make people suffer more. This supports research from Pambudi, Juanda, Priyarsono (2014), that the public did not believe that the government could control inflation after implementing redenomination, which it will not affect consumption patterns from the community. The results of a similar study by Turambi (2015), showed that redenomination and sanering as a policy of the monetary authority that was technically in nature and needed maturity and understanding from all levels of society, particularly to understand concepts and applications.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Concerns of the community are quite reasonable considering that the sanering policies that are put in place make people suffer more. This supports research from Pambudi, Juanda, Priyarsono (2014), that the public did not believe that the government could control inflation after implementing redenomination, which it will not affect consumption patterns from the community. The results of a similar study by Turambi (2015), showed that redenomination and sanering as a policy of the monetary authority that was technically in nature and needed maturity and understanding from all levels of society, particularly to understand concepts and applications.…”
Section: Discussionsupporting
confidence: 78%
“…Redenomination can be understood as sanering which can cause significant economic turmoil (Prabawani, 2017). Sanering is a policy of removing zeros on currency, but the deduction is not done on the price of goods so that people's purchasing power decreases (Pambudi, Juanda, Priyarsono, 2014). This understanding influences people's perspective or perception of government policies in implementing their policies.…”
mentioning
confidence: 99%
“…Redenomination had a potential to create hyper-inflation if it was conducted in a rush and controlled by the political motives or economy (Prabawani & Prihatini, 2014). Based on the survey by Pambudi et al, (2014) the people could not believe that the government woulld be able to control inflation after redenomination. When the inflation flew high, redenomination could drop the selling price so that inflation became the important predictor of redenomination (Mosley, 2005;Pambudi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the survey by Pambudi et al, (2014) the people could not believe that the government woulld be able to control inflation after redenomination. When the inflation flew high, redenomination could drop the selling price so that inflation became the important predictor of redenomination (Mosley, 2005;Pambudi et al, 2014). However, to support the success of redenomination, important factors other than the low level of inflation was needed: stability of the economy, a certainty of price stability, as well as a good socialization to the people (Lianto & Suryaputra, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ilmiah dilakukan dengan menggunakan data historis negara lain yang telah menerapkan kebijakan tersebut. Pambudi et al (2014) membahas mengenai faktor penentu keberhasilan penerapan redenominasi menggunakan pendekatan historikal 30 negara yang telah melakukan redenominasi dan percobaan langsung. Berdasarkan percobaan langsung tersebut diperoleh kesimpulan berupa ketika inflasi tinggi, redenominasi akan meningkatkan harga penjualan barang atau jasa.…”
Section: Pendahuluanunclassified